Late-infantile GM1 gangliosidosis: A case report. Issue 1 (7th January 2022) - Noh, Eu Seon; Park, Hye Mi; Kim, Min Sun; Park, Hyung-Doo; Cho, Sung Yoon; Jin, Dong-Kyu
Abstract: Rationale: Monosialotetrahexosylganglioside (GM1) gangliosidosis is a rare lysosomal storage disorder caused by the deficiency of ß-galactosidase. Because clinical symptoms of GM1 gangliosidosis overlap with other neurodevelopmental disorders, the diagnosis of this disease is not easy, specifically in late infantile GM1 gangliosidosis. This report described a case of late-infantile GM1 gangliosidosis mistaken for juvenile idiopathic arthritis. Patient concerns: A 16-year-old girl was referred to our hospital due to persistent multiple joint deformities and mental retardation, which could not be explained by juvenile idiopathic arthritis. Diagnosis: We made a diagnosis of late infantile GM1 gangliosidosis through enzyme assays and genetic testing after a skeletal survey. Interventions: The patient underwent cervical domeplasty and laminectomy for cord compression and received rehabilitation treatment. Outcomes: The patient is receiving multidisciplinary care at a tertiary center for variable skeletal disease and conditions associated with GM1 gangliosidosis. Lessons: Late infantile GM1 gangliosidosis should be considered in the differential diagnosis of progressive neurologic decline and skeletal dysostosis.